Green Coal Mining Techniques 2020 - Spearing, A.J.S (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Coal mining continues to make advances, especially in the areas of safety and environmental protection as a result of mining. This book contains nine peer-reviewed articles on green coal mining that address most of the important issues associated with improving coal mining. These issues include the protection of water above coal mines, both surface and ground water, and the subsidence that occurs during and after mining with methods to limit it and methods of rehabilitation. Additional issues include mine entry and production area support and methods to control gas emissions.